Aeroacoustics research in Europe: The CEAS-ASC report on 2022 highlights - Bennett, Gareth (My University, 2024)
The Council of European Aerospace Societies (CEAS) Aeroacoustics Specialists Committee (ASC) supports and promotes the interests of the scientific and industrial aeroacoustics community on a European scale and European aeronautics activities internationally. In this context, ‘‘aeroacoustics’’ encompasses all aerospace acoustics and related areas. Each year the committee highlights some of the research and development projects in Europe. This paper is a report on highlights of aeroacoustics research in Europe in 2022, compiled from information provided to the ASC of the CEAS. In addition, during 2022, a number of research programmes involving aeroacoustics were funded by the European Commission. Some of the highlights from these programmes are also summarized in this article, as well as highlights from other programmes funded by national programmes or by industry. Enquiries concerning all contributions should be addressed to the authors who are given at the end of each subsection.
PUBLISHED
Keywords: Aeroacoustics; Highlights; CEAS-ASC; Europe